تقييم تجربة استراتيجية استهداف التضخم في دول الاقتصاديات النامية والأسواق الناشئة(emde) - خلف الله, زكرياء; عياش, زبير (جامعة الوادي - University of Eloued, 2017)
تعتبر استراتيجية استهداف التضخم إحدى أهم بدائل أطر السياسة النقدية الحديثة التي تستخدمها البنوك المركزية للقضاء على ظاهرة التضخم التي تسود اقتصادياتها، حيث يقوم البنك المركزي بموجبها بإعلان صريح عن استهداف رقمي لمعدل التضخم مع توفير استقلالية أكبر للبنك المركزي، وكذا درجة عالية من الشفافية والمساءلة، وهذا من أجل تحقيق هدف الاستقرار في الأسعار. تهدف هذه الورقة البحثية إلى استخلاص أهم الدروس من تجربة دول الأسواق الناشئة والاقتصاديات النامية التي طبقت هذه الإستراتيجية، وهذا من أجل الوقوف على أهم المعوقات التي تعترض الأداء الجيد للسياسة النقدية المستهدفة للتضخم في هذه الدول، وكذا التحديات التي قد تواجهها في المستقبل، وتوصلت الورقة البحثية إلى عدد من النتائج كان أبرزها، أن 56% من دول العينة والتي تمثل 14 دولة من EMDEsكانت بعيدة كل البعد على تحقيق هدف الاستقرار في الأسعار سنة 2015، وهذا راجع إلى ضعف الإطار المؤسسي في البنوك المركزية، وعدم استجابة التضخم المحلي لإجراءات السياسة النقدية بسبب ضعف الأسواق المالية. we The inflation targeting strategy is one of the most important alternatives to the modern monetary policy frameworks used by central banks to eliminate the phenomenon of inflation that prevails in their economies, where the central bank, which explicitly declare the targeting of digital inflation rate provide greater independence of the Central Bank, as well as a high degree of transparency and accountability, In order to achieve the goal of price stability. This paper aims to draw the most important lessons from the experience of the emerging market countries and the developing economies that have implemented this strategy. This paper aims at identifying the main obstacles to the good performance of the monetary policy targeting inflation in these countries and the challenges that may face them in the future. A number of results, most notably, that 56% of the sample countries representing 14 countries of EMDEs were far from achieving the goal of price stability in 2015, due to weak institutional framework in central banks and the failure of domestic inflation response to monetary policy measures due to weakness Financial Markets.
مقال
Keywords: استراتيجية استهداف التضخم ، السياسة النقدية، البنوك المركزية.; Inflation targeting strategy , monetary policy, central banks.